Curricular points in the formation of ethnic identity of primary students from the perspective of popular culture - AXINTE, Luiza Lenuta; STAFIU, Natalia (Acta et Commentationes, Sciences of Education, 2026)
The present study aims to analyze the extent to which the current curricular documents for primary education support the formation of pupils’ ethnic identity from the perspective of folk culture. The research is based on a documentary analysis of the framework curriculum and school syllabi for preparatory to fourth grades, conducted using psychopedagogical and identity-based theoretical indicators. The analysis reveals that elements of folk culture are unevenly and mostly implicitly integrated into the primary school curriculum, being more visible within artistic and socio-human disciplines. Although there are favorable curricular premises for ethnic identity formation, they are not embedded within a coherent and explicit curricular framework. The findings highlight the need for a systematic integration of folk culture in primary education, in accordance with pupils’ developmental characteristics, and provide a basis for formulating curricular and didactic recommendations addressed to primary school teachers.